Behavioral Measures of Neurotoxicity - National Research Council (The National Academies Press, 1990)
Exposure to toxic chemicals—in the workplace and at home—is increasing every day. Human behavior can be affected by such exposure and can give important clues that a person or population is in danger. If we can understand the mechanisms of these changes, we can develop better ways of testing for toxic chemical exposure and, most important, better prevention programs. This volume explores the emerging field of neurobehavioral toxicology and the potential of behavior studies as a noninvasive and economical means for risk assessment and monitoring. Pioneers in this field explore its promise for detecting environmental toxins, protecting us from exposure, and treating those who are exposed.
Keywords: Environment and Environmental Studies

Improving Risk Communication: Working Papers - National Research Council (The National Academies Press, 1989)
Keywords: Behavioral and Social Sciences

Valuing Health Risks, Costs, and Benefits for Environmental Decision Making: Report of a Conference - National Research Council (The National Academies Press, 1990)
Keywords: Environment and Environmental Studies; Health and Medicine

Risks and Risk Governance in Shale Gas Development: Summary of Two Workshops - National Research Council (The National Academies Press, 2014)
Natural gas in deep shale formations, which can be developed by hydraulic fracturing and associated technologies (often collectively referred to as "fracking") is dramatically increasing production of natural gas in the United States, where significant gas deposits exist in formations that underlie many states. Major deposits of shale gas exist in many other countries as well. Proponents of shale gas development point to several kinds of benefits, for instance, to local economies and to national "energy independence". Shale gas development has also brought increasing expression of concerns about risks, including to human health, environmental quality, non-energy economic activities in shale regions, and community cohesion. Some of these potential risks are beginning to receive careful evaluation; others are not. Although the risks have not yet been fully characterized or all of them carefully analyzed, governments at all levels are making policy decisions, some of them hard to reverse, about shale gas development and/or how to manage the risks. Risks and Risk Governance in Shale Gas Development is the summary of two workshops convened in May and August 2013 by the National Research Council's Board on Environmental Change and Society to consider and assess claims about the levels and types of risk posed by shale gas development and about the adequacy of existing governance procedures. Participants from engineering, natural, and social scientific communities examined the range of risks and of social and decision-making issues in risk characterization and governance related to gas shale development. Central themes included risk governance in the context of (a) risks that emerge as shale gas development expands, and (b) incomplete or declining regulatory capacity in an era of budgetary stringency. This report summarizes the presentations on risk issues raised in the first workshop, the risk management and governance concepts presented at the second workshop, and the discussions at both workshops.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation; Environment and Environmental Studies

Developing New Contraceptives: Obstacles and Opportunities (The National Academies Press, 1990)
There are numerous reasons to hasten the introduction of new and improved contraceptives—from health concerns about the pill to the continuing medical liability crisis. Yet, U.S. organizations are far from taking a leadership position in funding, researching, and introducing new contraceptives—in fact, the United States lags behind Europe and even some developing countries in this field. Why is research and development of contraceptives stagnating? What must the nation do to energize this critical arena? This book presents an overall examination of contraceptive development in the United States—covering research, funding, regulation, product liability, and the effect of public opinion. The distinguished authoring committee presents a blueprint for substantial change, with specific policy recommendations that promise to gain the attention of specialists, the media, and the American public. The highly readable and well-organized volume will quickly become basic reading for legislators, government agencies, the pharmaceutical industry, private organizations, legal professionals, and researchers—everyone concerned about family planning, reproductive health, and the impact of the liability and regulatory systems on scientific innovations.
Keywords: Health and Medicine

The Social Impact of AIDS in the United States - National Research Council (The National Academies Press, 1993)
Europe's "Black Death" contributed to the rise of nation states, mercantile economies, and even the Reformation. Will the AIDS epidemic have similar dramatic effects on the social and political landscape of the twenty-first century? This readable volume looks at the impact of AIDS since its emergence and suggests its effects in the next decade, when a million or more Americans will likely die of the disease. The Social Impact of AIDS in the United States addresses some of the most sensitive and controversial issues in the public debate over AIDS. This landmark book explores how AIDS has affected fundamental policies and practices in our major institutions, examining:
Keywords: Health and Medicine

The Prevention and Treatment of Missing Data in Clinical Trials - National Research Council (The National Academies Press, 2010)
Randomized clinical trials are the primary tool for evaluating new medical interventions. Randomization provides for a fair comparison between treatment and control groups, balancing out, on average, distributions of known and unknown factors among the participants. Unfortunately, these studies often lack a substantial percentage of data. This missing data reduces the benefit provided by the randomization and introduces potential biases in the comparison of the treatment groups.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics

Environmentally Significant Consumption: Research Directions - National Research Council (The National Academies Press, 1997)
There has been much polemic about affluence, consumption, and the global environment. For some observers, "consumption" is at the root of global environmental threats: wealthy individuals and societies use far too much of the earth's resource base and should scale back their appetites to preserve the environment for future generations and allow a decent life for the rest of the world. Other observers see affluence as the way to escape environmental threats: economic development increases public pressure for environmental protection and makes capital available for environmentally benign technologies. The arguments are fed by conflicting beliefs, values, hopes, and fears—but surprisingly little scientific analysis. This book demonstrates that the relationship of consumption to the environment needs careful analysis by environmental and social scientists and conveys some of the excitement of treating the issue scientifically. It poses the key empirical questions: Which kinds of consumption are environmentally significant? Which actors are responsible for that consumption? What forces cause or explain environmentally significant consumption? How can it be changed? The book presents studies that open up important issues for empirical study: Are there any signs of saturation in the demand for travel in wealthy countries? What is the relationship between environmental consumption and human well-being? To what extent do people in developing countries emulate American consumption styles? The book also suggests broad strategies that scientists and research sponsors can use to better inform future debates about the environment, development, and consumption.
Keywords: Behavioral and Social Sciences; Energy and Energy Conservation

Contact Lens Use Under Adverse Conditions: Applications in Military Aviation - National Research Council (The National Academies Press, 1990)
Keywords: Health and Medicine

Ethical Considerations for Research on Housing-Related Health Hazards Involving Children - National Research Council; Institute of Medicine (The National Academies Press, 2005)
Ethical Considerations for Research on Housing-Related Health Hazards Involving Children explores the ethical issues posed when conducting research designed to identify, understand, or ameliorate housing-related health hazards among children. Such research involves children as subjects and is conducted in the home and in communities. It is often conducted with children in low-income families given the disproportionate prevalence of housing-related conditions such as lead poisoning, asthma, and fatal injuries among these children. This book emphasizes five key elements to address the particular ethical concerns raised by these characteristics: involving the affected community in the research and responding to their concerns; ensuring that parents understand the essential elements of the research; adopting uniform federal guidelines for such research by all sponsors (Subpart D of 45 CFR 46); providing guidance on key terms in the regulations; and viewing research oversight as a system with important roles for researchers, IRBs and their research institutions, sponsors and regulators of research, and the community.
Keywords: Behavioral and Social Sciences; Health and Medicine; Policy for Science and Technology

Children's Mental Health and the Life Course Model: A Virtual Workshop Series: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
With rapidly rising rates of mental health disorders, changing patterns of occurrence, and increasing levels of morbidity, the need for a better understanding of the developmental origins and influence of mental health on children’s behavioral health outcomes has become critical. This need for better understanding extends to both the growing prevalence of mental health disorders as well as the role and impact of neurodevelopmental pathways in their onset and expression. Addressing these changes in disease patterns and effects on children and families will require a multifaceted approach that goes beyond simply making changes to clinical care or adding personnel to the health services system. New policies, financing, and implementation can put established best practices and numerous research findings from around the country into action.
Keywords: Health and Medicine; Behavioral and Social Sciences

New Tools for Environmental Protection: Education, Information, and Voluntary Measures - National Research Council (The National Academies Press, 2002)
Many people believe that environmental regulation has passed a point of diminishing returns: the quick fixes have been achieved and the main sources of pollution are shifting from large "point sources" to more diffuse sources that are more difficult and expensive to regulate. The political climate has also changed in the United States since the 1970s in ways that provide impetus to seek alternatives to regulation. This book examines the potential of some of these "new tools" that emphasize education, information, and voluntary measures. Contributors summarize what we know about the effectiveness of these tools, both individually and in combination with regulatory and economic policy instruments. They also extract practical lessons from this knowledge and consider what is needed to make these tools more effective.The book will be of interest to environmental policy practitioners and to researchers and students concerned with applying social and behavioral sciences knowledge to improve environmental quality.
Keywords: Environment and Environmental Studies

Considerations in Contact Lens Use Under Adverse Conditions: Proceedings of a Symposium - National Research Council (The National Academies Press, 1991)
This book summarizes current understanding of the scientific, clinical, and technical issues surrounding the use of contact lenses. It discusses the special occupational conditions experienced by military personnel, particularly in extreme environments, that give rise to the question of whether or not to use contact lenses. Experts in optometry, ophthalmology, visual psychophysics, and engineering describe recent developments in design and use; and representatives of the military services provide examples of actual situations in aerospace settings. Considerations in Contact Lens Use Under Adverse Conditions will be of particular interest to those involved in the design of contact lenses and those responsible for occupational safety and health matters in the private sector.
Keywords: Health and Medicine

Malaria Control During Mass Population Movements and Natural Disasters - National Research Council (The National Academies Press, 2003)
Admittedly, the world and the nature of forced migration have changed a great deal over the last two decades. The relevance of data accumulated during that time period can now be called into question. The roundtable and the Program on Forced Migration at the Mailman School of Public Health of Columbia University have commissioned a series of epidemiological reviews on priority public health problems for forced migrants that will update the state of knowledge. Malaria Control During Mass Population Movements and Natural Disasters -- the first in the series, provides a basic overview of the state of knowledge of epidemiology of malaria and public health interventions and practices for controlling the disease in situations involving forced migration and conflict.
Keywords: Health and Medicine

Ergonomic Models of Anthropometry, Human Biomechanics and Operator-Equipment Interfaces: Proceedings of a Workshop - National Research Council (The National Academies Press, 1988)
Keywords: Behavioral and Social Sciences

Language and Machines: Computers in Translation and Linguistics (The National Academies Press, 1966)
Keywords: Engineering and Technology

Explaining Divergent Levels of Longevity in High-Income Countries - National Research Council (The National Academies Press, 2011)
During the last 25 years, life expectancy at age 50 in the United States has been rising, but at a slower pace than in many other high-income countries, such as Japan and Australia. This difference is particularly notable given that the United States spends more on health care than any other nation. Concerned about this divergence, the National Institute on Aging asked the National Research Council to examine evidence on its possible causes.
Keywords: Behavioral and Social Sciences; Health and Medicine

Understanding Risk: Informing Decisions in a Democratic Society - National Research Council (The National Academies Press, 1996)
Understanding Risk addresses a central dilemma of risk decisionmaking in a democracy: detailed scientific and technical information is essential for making decisions, but the people who make and live with those decisions are not scientists. The key task of risk characterization is to provide needed and appropriate information to decisionmakers and the public. This important new volume illustrates that making risks understandable to the public involves much more than translating scientific knowledge. The volume also draws conclusions about what society should expect from risk characterization and offers clear guidelines and principles for informing the wide variety of risk decisions that face our increasingly technological society.
Keywords: Environment and Environmental Studies

Global Environmental Change: Understanding the Human Dimensions - National Research Council (The National Academies Press, 1992)
Global environmental change often seems to be the most carefully examined issue of our time. Yet understanding the human side—human causes of and responses to environmental change—has not yet received sustained attention. Global Environmental Change offers a strategy for combining the efforts of natural and social scientists to better understand how our actions influence global change and how global change influences us. The volume is accessible to the nonscientist and provides a wide range of examples and case studies. It explores how the attitudes and actions of individuals, governments, and organizations intertwine to leave their mark on the health of the planet. The book focuses on establishing a framework for this new field of study, identifying problems that must be overcome if we are to deepen our understanding of the human dimensions of global change, presenting conclusions and recommendations.
Keywords: Environment and Environmental Studies

Protecting Youth at Work: Health, Safety, and Development of Working Children and Adolescents in the United States (The National Academies Press, 1998)
In Massachusetts, a 12-year-old girl delivering newspapers is killed when a car strikes her bicycle. In Los Angeles, a 14-year-old boy repeatedly falls asleep in class, exhausted from his evening job. Although children and adolescents may benefit from working, there may also be negative social effects and sometimes danger in their jobs. Protecting Youth at Work looks at what is known about work done by children and adolescents and the effects of that work on their physical and emotional health and social functioning. The committee recommends specific initiatives for legislators, regulators, researchers, and employers. This book provides historical perspective on working children and adolescents in America and explores the framework of child labor laws that govern that work. The committee presents a wide range of data and analysis on the scope of youth employment, factors that put children and adolescents at risk in the workplace, and the positive and negative effects of employment, including data on educational attainment and lifestyle choices. Protecting Youth at Work also includes discussions of special issues for minority and disadvantaged youth, young workers in agriculture, and children who work in family-owned businesses.
Keywords: Behavioral and Social Sciences; Health and Medicine